Effects of organic ligands and background electrolytes on barite dissolution. (1st July 2019) - Ouyang, Bingjie; Renock, Devon; Akob, Denise M.
Abstract: Barite dissolution rates and features were investigated under conditions that combine a variety of organic ligands with different background electrolyte solutions. The organic ligands included low molecular weight organic compounds (LMWO) that can be produced by halophilic bacteria and are common in natural environments, as well as synthetic chelators that were previously studied in barite dissolution. Background electrolyte solutions included deionized water, 0.72 M NaCl and 2 M NaCl solutions designed to simulate freshwater, seawater, and brine fluids, respectively. Barite dissolution rates and corresponding rate constants normalized for saturation states were calculated for most experiments. Equal or lower rates and rate constants for pure LMWO relative to controls at all background electrolyte concentrations and pH values indicated that LMWO do not promote barite dissolution. Synthetic chelators showed higher rates and rate constants at pH 10 at static conditions than controls, indicating enhanced barite dissolution. Distinctive etch pit morphologies on the barite (0 0 1) face were observed in the presence of synthetic chelators, suggesting a direct contact dissolution mechanism by synthetic chelators. The effect of synthetic chelators on barite dissolution was significantly reduced in the presence of 2 M NaCl and/or at pH 6.5 due to salting out effects. Under hypersaline conditions, barite dissolution rates and rate constants by bacterial activities were up to four times higher than those of synthetic chelators. The wide range of conditions studied in this work provides insights into prediction of barite dissolution behavior in various natural environments as well as in industrial treatment procedures.